An oral bait vaccination approach for the Tasmanian devil facial tumor diseases. (2nd January 2020) - Flies, Andrew S.; Flies, Emily J.; Fox, Samantha; Gilbert, Amy; Johnson, Shylo R.; Liu, Guei-Sheung; Lyons, A. Bruce; Patchett, Amanda L.; Pemberton, David; Pye, Ruth J.
ABSTRACT: Introduction : The Tasmanian devil ( Sarcophilus harrisii ) is the largest extant carnivorous marsupial. Since 1996, its population has declined by 77% primarily due to a clonal transmissible tumor, known as devil facial tumor (DFT1) disease. In 2014, a second transmissible devil facial tumor (DFT2) was discovered. DFT1 and DFT2 are nearly 100% fatal. Areas covered : We review DFT control approaches and propose a rabies-style oral bait vaccine (OBV) platform for DFTs. This approach has an extensive safety record and was a primary tool in large-scale rabies virus elimination from wild carnivores across diverse landscapes. Like rabies virus, DFTs are transmitted by oral contact, so immunizing the oral cavity and stimulating resident memory cells could be advantageous. Additionally, exposing infected devils that already have tumors to OBVs could serve as an oncolytic virus immunotherapy. The primary challenges may be identifying appropriate DFT-specific antigens and optimization of field delivery methods. Expert opinion : DFT2 is currently found on a peninsula in southern Tasmania, so an OBV that could eliminate DFT2 should be the priority for this vaccine approach. Translation of an OBV approach to control DFTs will be challenging, but the approach is feasible for combatting ongoing and future disease threats.